2017
DOI: 10.1111/opo.12359
|View full text |Cite
|
Sign up to set email alerts
|

Differences in retinal shape between East Asian and Caucasian eyes

Abstract: East Asians had steeper retinas than Caucasians. The horizontal meridian had steeper retinas than the vertical meridian. Myopes had steeper retinas than emmetropes. Racial differences in retinal shape in both emmetropes and myopes, combined with the high prevalence of myopia in East Asia, suggest that retinal shape may play a role in myopia development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 29 publications
6
30
0
Order By: Relevance
“…A further difference between the current study and the partial coherence interferometry method is that in the latter, race was found to affect shape, with East Asians having steeper retinas than Caucasians with a mean difference in vertex radii of curvature of -0.7 ± 0.5 mm [24].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…A further difference between the current study and the partial coherence interferometry method is that in the latter, race was found to affect shape, with East Asians having steeper retinas than Caucasians with a mean difference in vertex radii of curvature of -0.7 ± 0.5 mm [24].…”
Section: Discussionmentioning
confidence: 82%
“…We note that our "partial coherence interferometry" method for estimating retinal shape by combining peripheral axial length measurements with symmetric ocular modelling found meridional differences, with retinas being steeper by about 1.5 mm vertex radius of curvature in the horizontal meridian than in the vertical meridian in an East Asian group, and with the shapes being strongly correlated with peripheral refraction (steeper retinas accompanying higher relative peripheral hyperopia) [23]. A further study with a combined East Asian/Caucasian group found a difference in vertex radius of curvature of 1.2 mm between meridians [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies involving humans have investigated peripheral refraction, with only a few looking at peripheral refraction and retinal shape in combination. Verkicharla et al reported that peripheral refraction, peripheral eye lengths, and retinal shapes measured from partial coherence interferometry were significantly affected by race, as well as by meridian and refraction. East Asians were found to have steeper retinas and greater relative peripheral hyperopia than Caucasians, with steepness being greater along the horizontal meridian than the vertical meridian.…”
Section: Peripheral Defocusmentioning
confidence: 99%